Comparison of 627 patients with right- and left-sided colon cancer in China: Differences in clinicopathology, recurrence, and survival. Issue 1 (25th March 2017) - Qin, Qiong; Yang, Lin; Sun, Yong-Kun; Ying, Jian-Ming; Song, Yan; Zhang, Wen; Wang, Jin-Wan; Zhou, Ai-Ping
Abstract: Objective: Recent studies have reported increased mortality for right-sided colon cancers; however, the results are conflicting for different stage tumors. We examined the differences in clinicopathology between right- and left-sided colon cancers and the relationships between colon cancer location (right- and left-side) and 5-year disease-free survival (DFS) and overall survival (OS). Methods: We identified patients from 2005 to 2008 with stage II/III colon cancer who underwent surgery for curative intent. We explored the impact of the tumor location on the postoperative DFS and OS using univariate and multivariate analyses. Results: Of 627 patients, 50.6% (317/627) had right-sided colon cancer. These patients were more likely to have weight loss, second primary tumor, elevated preoperative carbohydrate antigen 19-9 (CA19-9), increased incidence of non-adenocarcinoma, more poorly differentiated tumors, vascular invasion, defective mismatch repair, and a lighter smoking history ( P  < 0.05). Right-sided colon cancer had a higher recurrence incidence compared with left-sided cancer (30.6% vs. 23.2%, P  = 0.037), particularly with multiple metastatic sites in the first recurrence (17.5% vs. 5.6%, P  = 0.020). Kaplan–Meier survival curves demonstrated a significant difference in the 5-year DFS rate between right- and left-sided cancers across all stages (68.1% vs. 75.2%, P  = 0.043). However, there was no significant difference in the 5-year OS rate between the two groups (73.8% vs. 79.0%, P  = 0.103). Subgroup analysis demonstrated that patients with left-sided colon cancer had a significantly better 5-year DFS and OS rates compared with those with right-sided disease at stage III (64.3% vs. 46.8%, P  = 0.002; 69.5% vs. 53.5%, P  = 0.006, respectively); there were no significant differences in the 5-year DFS and OS rates at stage II (85.2% vs. 85.9%, P  = 0.819; 89.8% vs. 88.5%, P  = 0.803, respectively). Adjusted Cox regression analysis showed no significant differences in the 5-year OS and DFS rates for stage II [hazard ratio ( HR ) = 1.203, 95% confidence interval ( CI ): 0.605–2.391, P  = 0.598; HR  = 0.980, 95% CI : 0.542–1.774, P  = 0.948, respectively] or all stages combined ( HR = 0.867, 95% CI : 0.613–1.227, P = 0.421; HR = 0.832, 95% CI : 0.606–1.142, P = 0.255, respectively). However, stage III left-sided cancer had higher 5-year OS and DFS rates ( HR  = 0.626, 95% CI : 0.414–0.948, P  = 0.027; HR  = 0.630, 95% CI : 0.428–0.926, P  = 0.019, respectively). Conclusion: We found that right- and left-sided colon cancers had significantly different clinicopathological characteristics. Right-sided colon cancer had a higher incidence of recurrence than left-sided disease. Patients with stage III right-sided colon cancer had a worse prognosis compared with those with stage III left-sided colon cancer.